2020
DOI: 10.1109/access.2020.3036123
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “An Efficient ABE Scheme With Verifiable Outsourced Encryption and Decryption”

Abstract: , Li et al.[1] proposed a secure outsourcing algorithm for modular exponentiation in one single untrusted server model and a new method of generating transformation keys. They claimed that their solution can securely outsource encryption and decryption to untrusted ESP (encryption service providers) and DSP (decryption service providers), leaving only a constant number of simple operations for the DO (data owner) and eligible users to perform locally. In addition, both DO and qualified users can check the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…eir scheme not only reduces the storage cost of mobile devices but also requires only a small amount of computing overhead to complete the decryption. However, Guo et al [13] found that there was a security problem in Li et al's scheme [12] and put forward an improved scheme. Fan et al [14] proposed a secure and effective outsourcing computing algorithm to solve the problem of a large amount of computing in existing schemes for data encrypting on mobile devices.…”
Section: Related Workmentioning
confidence: 99%
“…eir scheme not only reduces the storage cost of mobile devices but also requires only a small amount of computing overhead to complete the decryption. However, Guo et al [13] found that there was a security problem in Li et al's scheme [12] and put forward an improved scheme. Fan et al [14] proposed a secure and effective outsourcing computing algorithm to solve the problem of a large amount of computing in existing schemes for data encrypting on mobile devices.…”
Section: Related Workmentioning
confidence: 99%